Photodegradation of some Antibiotics and Industrial Dye by Visible Light of Highly Active Synthesized PAni/TiO2 Nanocomposite Photocatalyst - Mahmoud, Auwal Adamu; Ali, S.B; Ajiya, D.A.; Muhammad, M (Jurnal Bio-Geo Material Dan Energi, 2025)
The presence of pharmaceuticals and dyes in the environment poses significant threats to human health and ecosystems. This study develops a novel Polyaniline/Titanium Dioxide (PAni/TiO₂) nanocomposite photocatalyst for the efficient photodegradation of tetracycline and methylene blue. Characterization techniques, including FTIR, FESEM, EDX, DRS, and TGA, confirmed the successful formation of the nanocomposite. Under UV and visible light irradiation, The optimal condition for maximum tetracycline and methylene blue degradation efficiency was obtained to be 92% and 95%, respectively, with 100 mg  of PAni/TiO2 nanocomposite, 100 ml  of Tetracycline, and pH 7.0 after 120 min of exposure to UV and visible light. Optimum reaction conditions, including catalyst concentration, initial dye concentration, and reaction time, were investigated. This research demonstrates the potential of PAni/TiO₂ nanocomposite as a promising photocatalyst for the degradation of organic pollutants